Presidential Address. “To the Stars in the Twinkling Foam”: A Consideration of the Act of Making History in History-Breaking Times - Bryden, P. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2022)
In this presidential address to the CHA, Penny Bryden considers the ways historians research, write, and use history. She argues that when the structure of our output changes, so too does the way audiences understand it.